GAIA AND EARTH JUSTICE: Earth as a Natureculture for ‘Harmony with Nature’ - Im, Ji-Yeon; Seo, Yunho (Journal of Dharma, 2021)
The purpose of this paper is to explore the possibility of a sustainable earth of the UN SDGs Planet agenda through Gaia theory, and to criticize and supplement the theoretical foundation of earth jurisprudence from the secularized Gaia perspective. The ethical direction of earth justice for ‘Harmony with Nature’ can be found through the combination of Gaia theory and earth jurisprudence. The ethical and practical implications of the Gaia theory and earth jurisprudence for ‘Harmony with Nature’ are as follows. First, the Gaia theory aims to secularize the concept of a divine Mother Earth. Second, Gaia has a naturecultural perspective that integrates humans and non-humans beyond the dichotomy between nature and culture. Third, earth jurisprudence based on the secularized Gaia can properly realize earth justice that recognizes the rights of nature.